2016
DOI: 10.21037/jss.2016.06.05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cement augmentation on the mechanical stability of multilevel spine after vertebral compression fracture

Abstract: Background: Studies on the effects of cement augmentation or vertebroplasty on multi-level spine after vertebral compression fractures are lacking. This paper seeks to establish a 3-vertebrae ovine model to determine the impact of compression fracture on spine biomechanics, and to discover if cement augmentation can restore mechanical stability to fractured spine.Methods: Five lumbar spine segments (L1-L3) were obtained from 5-year-old female Merino sheep.Standardized wedge-compression fractures were generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Vertebral bodies treating with PVP will increase their mobility in all directions due to their limited height recovery. Tan E et al (34)found in a goat lumbar spine PVP model test that postoperative range of motion (ROM) and neutral zone (NZ) increased in all directions of motion after fracture, and cement augmentation could not restore the normal biomechanics of the spine. Jhong GH et al (35)found that AVHR increased ROM in extension in a lumbar spine model test.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebral bodies treating with PVP will increase their mobility in all directions due to their limited height recovery. Tan E et al (34)found in a goat lumbar spine PVP model test that postoperative range of motion (ROM) and neutral zone (NZ) increased in all directions of motion after fracture, and cement augmentation could not restore the normal biomechanics of the spine. Jhong GH et al (35)found that AVHR increased ROM in extension in a lumbar spine model test.…”
Section: Discussionmentioning
confidence: 99%
“…For animal models, the lumbar vertebrae of goats are considered anatomically and biomechanically similar to humans [24]. Many related studies have utilized goats as experimental subjects, including the development of a vertebral bone defect model [25], an experimental model for PV procedures [26], and the spinal mechanical stability after cement augmentation [27]. Accordingly, we choose goats as an ex vivo animal model for the evaluation of the efficacy of APV.…”
Section: Introductionmentioning
confidence: 99%
“…The main factors associated with OLVF are a decrease in bone density, bone quality deterioration, and bone microstructure degeneration caused by osteoporosis [ 1 , 2 ]. Since the risk of osteoporosis increases with age, the number of patients with osteoporosis and those who develop OLVF will continue to increase as life expectancy increases [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%